An Antipodean Imaginary for Architecture+Philosophy: Ficto-Critical Approaches to Design Practice Research - Hélène Frichot; Julieanna Preston; Michael Spooner; Sean Pickersgill; Zuzana Kovar; Ceri Hann; Megg Evans (Footprint)
This is a collaborative essay that presents the design practice research of six postgraduate researchers (past and present), who have been working within the Architecture+Philosophy research stream at the School of Architecture, RMIT University, Melbourne. What unites the projects is an aspiration to maintain a creative relationship between architectural design project research and critical theory, with an emphasis on transdisciplinary potentialities.